2014
DOI: 10.1002/ejoc.201402816
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Highly Fluoroalkyl‐Functionalized Oligoporphyrin Systems

Abstract: Four different multiporphyrin systems have been synthesized and characterized. Highly fluoroalkyl‐functionalized porphyrins are the most complex objects so far to have exhibited quantum wave nature. We have functionalized larger oligoporphyrin systems with fluoroalkyl chains to increase their mass and minimize their intermolecular interactions. The to‐some‐extent random substitution of fluorine atoms at the periphery of the oligoporphyrins results in libraries consisting of molecules varying in both the number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Despite their fragility, thermal beams of nucleotides 24 and individual amino acids 25 have been prepared successfully for mass spectrometry before. It has also been recently demonstrated 26–28 that highly fluorinated alkyl tags can facilitate molecular volatilization. It is interesting to note that fluorination of biomolecules is a frequently used technique to enhance the stability of proteins against chemical and thermal denaturation, while maintaining the molecule's structure and biological activity 29 .…”
Section: Main Textmentioning
confidence: 99%
“…Despite their fragility, thermal beams of nucleotides 24 and individual amino acids 25 have been prepared successfully for mass spectrometry before. It has also been recently demonstrated 26–28 that highly fluorinated alkyl tags can facilitate molecular volatilization. It is interesting to note that fluorination of biomolecules is a frequently used technique to enhance the stability of proteins against chemical and thermal denaturation, while maintaining the molecule's structure and biological activity 29 .…”
Section: Main Textmentioning
confidence: 99%
“…[3,4] At a fixed molecular beam velocity, mass variation implies a controlled tuning of de Broglie wavelengths (λ dB = h/mv). We compare two molecular libraries [27] as shown in Fig. 1: a tetrahedral arrangement of four zinc-coordinated porphyrins arranged around one tetraphenylmethane core and a planar pentaporphyrin.…”
Section: Functionalization Of Two Oligoporphyrinsmentioning
confidence: 99%
“…In our present work, we focus on the question how to derivatize biomolecular structures such that their sublimation enthalpy is reduced and their thermal stability increased. Perfluoroalkyl functionalization of individual molecules is expected to reduce the binding to neighbouring particles and surfaces because earlier studies have shown that it enhances the volatility of large organic compounds . Here, we apply this strategy for the first time to oligopeptides and study its influence on their volatility.…”
Section: Introductionmentioning
confidence: 99%
“…Perfluoroalkyl functionalization of individual molecules is expected to reduce the binding to neighbouring particles and surfaces because earlier studies have shown that it enhances the volatility of large organic compounds. [17,[59][60][61] Here, we apply this strategy for the first time to oligopeptides and study its influence on their volatility.…”
Section: Introductionmentioning
confidence: 99%